Ventilation Strategies to Ensure Thermal Comfort for Users in School Buildings: A Critical Review - María Teresa Aguilar-Carrasco; Remedios María López-Lovillo; Rafael Suárez; Ángel Luis León-Rodríguez (Applied Sciences)
People spend most of their time indoors, where air quality is crucial to health. In this context, this study conducts a critical review of ventilation strategies in schools to ensure air quality, as well as to guarantee students’ thermal comfort. Based on a bibliographical review, strategies from previous studies are identified and evaluated in order to determine their advantages. After a detailed search, a total of 19 articles were selected, which provides a thorough analysis of the ventilation strategies in school buildings considering thermal comfort. The identified strategies were categorized into natural, mechanical, and hybrid types. The results reveal a prevalence of natural ventilation, which accounts for over 50% of strategies in all climates. Mechanical ventilation is less common and is applicable to around 30% of cases. Hybrid strategies, combining natural and mechanical ventilation, are the least used and only appear in oceanic climates, with a usage rate of 20%. Most studies highlight the lack of air conditioning in many schools, making adequate thermal stress management through ventilation crucial. The results analyzed clearly show a lack of studies with optimal results whose ventilation strategies can be replicated in other similar educational buildings, ensuring thermal comfort and air quality.